2017
DOI: 10.1371/journal.pgen.1006631
|View full text |Cite
|
Sign up to set email alerts
|

SEPT12 phosphorylation results in loss of the septin ring/sperm annulus, defective sperm motility and poor male fertility

Abstract: Septins are critical for numerous cellular processes through the formation of heteromeric filaments and rings indicating the importance of structural regulators in septin assembly. Several posttranslational modifications (PTMs) mediate the dynamics of septin filaments in yeast. However, little is known about the role of PTMs in regulating mammalian septin assembly, and the in vivo significance of PTMs on mammalian septin assembly and function remains unknown. Here, we showed that SEPT12 was phosphorylated on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 37 publications
(61 reference statements)
0
41
0
2
Order By: Relevance
“…One way to compartmentalize membranes is through membrane diffusion barriers [7981]. Diffusion barriers have been postulated at the base of cilia [41], dendritic spines [82], and at the tip of mating projections during chemotropism [83], at the mother-bud neck in S. cerevisiae [39, 84], and the annulus in spermatozoa [85]. Interestingly, septins localize to each of these structures, and have been proposed to contribute to the membrane diffusion barrier [86].…”
Section: How Cells Use Micron Scale Curvaturementioning
confidence: 99%
See 1 more Smart Citation
“…One way to compartmentalize membranes is through membrane diffusion barriers [7981]. Diffusion barriers have been postulated at the base of cilia [41], dendritic spines [82], and at the tip of mating projections during chemotropism [83], at the mother-bud neck in S. cerevisiae [39, 84], and the annulus in spermatozoa [85]. Interestingly, septins localize to each of these structures, and have been proposed to contribute to the membrane diffusion barrier [86].…”
Section: How Cells Use Micron Scale Curvaturementioning
confidence: 99%
“…al. showed that phosphorylation within the GTP-binding domain of Sept12 abolished septin ring formation at the annulus in sperm [85], further highlighting the importance of septin regulation by phosphorylation. Interestingly, an acetylation/SUMO-ylation switch was found to regulate Cdc11 localization from the bud scar to the new incipient bud site in S. cerevisiae [94].…”
Section: Regulation Of Micron-scale Curvature Sensorsmentioning
confidence: 99%
“…Given the range of cellular functions associated with septins, it is not surprising that a variety of diseases are linked to loss or gain of septin functions. Abnormalities in septin expression are linked to male infertility, hereditary neuralgic amyotrophy, neurodevelopmental disorders, Alzheimer, and Parkinson [4,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Embora os filamentos de septinas sejam as estruturas de maior importância funcional, pouco se sabe sobre a formação dos complexos, montagem e desmontagem dos filamentos e especificidade da interação septina-septina e septinas-proteínas parceiras [45]. Estudos realizados em levedura demonstraram que modificações pós-traducionais, como a sumoilação, fosforilação e acetilação são capazes de modular a dinâmica da formação dos filamentos de septinas [46]. As septinas da Saccharomyces cerevisiae são sumoiladas durante o ciclo celular, no entanto mutações nos sítios de sumoilação interferem na desmontagem do anel de septinas no sítio anterior ao ciclo de divisão [47].…”
Section: Formação Dos Complexos De Septinas Humanasunclassified
“…Em humanos muitos estudos identificaram modificações pós-traducionais em septinas, no entanto o seu papel na montagem dos filamentos in vivo é desconhecido. Os exemplos reportados na literatura são: fosforilação da SEPT3 pela proteína quinase dependente de cGMP 1 (PKG-I) em terminais nervosos [49,50], fosforilação da SEPT4 pela glicogênio sintase quinase (GSK3) em espermatozoides [51], ubiquitinação da SEPT5 pela proteína de ligação a Parkin E3 que causa a sua degradação [27] e fosforilação da SEPT12 pela proteína quinase A em testículos [46].…”
Section: Formação Dos Complexos De Septinas Humanasunclassified